Long interspersed nuclear element 1 hypomethylation has novel prognostic value and potential utility in liquid biopsy for oral cavity cancer - Kiyoshi Misawa; Satoshi Yamada; Masato Mima; Takuya Nakagawa; Tomoya Kurokawa; Atsushi Imai; Daiki Mochizuki; Daichi Shinmura; Taiki Yamada; Junya Kita; Ryuji Ishikawa; Yuki Yamaguchi; et al. (BMC, 2020)
Abstract Background New biomarkers are urgently needed to improve personalized treatment approaches for head and neck squamous cell carcinoma (HNSCC). Global DNA hypomethylation has wide-ranging functions in multistep carcinogenesis, and the hypomethylation of long interspersed nucleotide element-1 (LINE-1) is related to increased retrotransposon activity and induced genome instability. However, little information is available regarding LINE-1 hypomethylation and its prognostic implications in HNSCC. Methods In this study, we analyzed LINE-1 hypomethylation levels in a well-characterized dataset of 317 primary HNSCC tissues and 225 matched pairs of normal mucosa tissues, along with five oral cavity cancer (OCC) circulating tumor DNA (ctDNA) samples using quantitative real-time methylation and unmethylation PCR. The analysis was performed according to various clinical characteristics and prognostic implications. Results The results demonstrated that LINE-1 hypomethylation levels were significantly higher in the HNSCC tissues than in corresponding normal tissues from the same individuals (P < 0.001). Univariate analysis revealed that high levels of LINE-1 hypomethylation were correlated with poor disease-free survival (DFS; log-rank test, P = 0.038), whereas multivariate analysis demonstrated that they were significant independent prognostic factor for DFS (hazard ratio: 2.10, 95% confidence interval: 1.02-4.36; P = 0.045). Moreover, samples with high LINE-1 hypomethylation levels exhibited the greatest decrease in 5-hydroxymethylcytosine (5-hmC) levels and increase in tumor-suppressor gene methylation index (P = 0.006 and P < 0.001, respectively). Further, ctDNA studies also showed that LINE-1 hypomethylation had high predictive ability in OCC. Conclusions LINE-1 hypomethylation is associated with a higher risk of early OCC relapse, and is hence, a potential predictive biomarker for OCC. Furthermore, 5-hmC levels also exhibited predictive potential in OCC, based on their inverse correlation with LINE-1 hypomethylation levels. LINE-1 hypomethylation analysis, therefore, has applications in determining patient prognosis and real-time surveillance of disease recurrence, and could serve as an alternative method for OCC screening.